Cloud Computing Concepts and Practices - Sehgal, Naresh Kumar; Bhatt, Pramod Chandra P. (Springer International Publishing : Imprint: Springer, 2018)
This book provides readers with an overview of Cloud Computing, starting with historical background on mainframe computers and early networking protocols, leading to current concerns such as hardware and systems security, performance, emerging areas of IoT, Edge Computing etc. Readers will benefit from the in-depth discussion of cloud computing usage and the underlying architecture, with focus on best practices for using a dynamic cloud infrastructure, cloud operations management and cloud security. The authors explain carefully the "why's and how's" of Cloud Computing, so engineers will find this book and invaluable introduction to the topic. Provides practical guidance for software developers engaged in migrating in-house applications to Public Cloud; Describes for IT managers how to improve their Cloud Computing infrastructures; Includes coverage of security concerns with Cloud operating models; Uses several casestudies to illustrate the "why's and how's" of migrating to the Cloud.